1997
DOI: 10.1177/017084069701800305
|View full text |Cite
|
Sign up to set email alerts
|

Harmony and Patriarchy: The Cultural Basis for 'Paternalistic Headship' Among the Overseas Chinese

Abstract: This paper outlines a model of leadership attuned to the cultural specificities of the Overseas Chinese (OSC) context. The model is developed in a contrastive mode to U.S. approaches to leadership which are depicted as being culturally bounded and non-transferable to the OSC situation. The model is extrapolated from the persisting cultural values and traditions still prevalent in OSC organizations and management style. The concept of headship is heuristically adopted to demarcate the underlying orientation tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
197
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(214 citation statements)
references
References 33 publications
(36 reference statements)
6
197
0
11
Order By: Relevance
“…A number of authors make a similar case for the Diaspora Chinese in Southeast Asia (e.g. Freedman 1979b;Redding 1990;Kao 1993;Redding 1996;Koon 1997;Westwood 1997). Different dimensions of Confucianism have been identified (for overviews of traditional Chinese values see Hofstede and Bond 1988;Redding 1990;Kao 1993).…”
Section: The Confucian Inheritancementioning
confidence: 96%
See 1 more Smart Citation
“…A number of authors make a similar case for the Diaspora Chinese in Southeast Asia (e.g. Freedman 1979b;Redding 1990;Kao 1993;Redding 1996;Koon 1997;Westwood 1997). Different dimensions of Confucianism have been identified (for overviews of traditional Chinese values see Hofstede and Bond 1988;Redding 1990;Kao 1993).…”
Section: The Confucian Inheritancementioning
confidence: 96%
“…These practices entail a distinct organisational form (Redding 1990, p. 3, 42) and leadership model (Westwood 1997) and Hughes 1996, pp. 52-53).…”
Section: The Spirit Of Overseas Chinese Capitalismmentioning
confidence: 99%
“…Paternalistic leadership, proposed by Farh and Cheng [4] on the basis of studies from Redding [33], Cheng [34], and Westwood [3], is widespread in Chinese society. Paternalistic leadership could be defined as a style of leadership characterized by high discipline and authoritarianism, fatherly benevolence and high moral standards [4].…”
Section: Paternalistic Leadershipmentioning
confidence: 99%
“…From a historical viewpoint, Spence and Chin [2] suggested that the 20th century was the century of China, and we believe that they referred to the significant political, social, cultural, and even economic transformations which China has had since the end of the Qing Dynasty in 1912. As a typical style of leadership in the Chinese community, paternalistic leadership has already attracted a great deal of attention [3][4][5], and could be strongly explained in high power distance and collectivist cultures [6][7][8]. Current studies on paternalistic leadership tended to focus at the individual level of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Decisions are made at the top (Lu, 1998;Scarborough, 1998), and interaction among individuals and organisations is built upon trust and is highly personalised (Schermerhorn and Bond, 1992). As such, participative management approaches are not as common (Pun et al, 2000;Redding and Richardson, 1986;Westwood, 1997). Chinese managers tend to be more people-and relationship-oriented than US managers (Lockett, 1988;Wah, 2001).…”
Section: Career Successmentioning
confidence: 99%